Factors affecting use of computer technology in rural secondary schools by ODL students who are secondary school teachers in Mbire district of Mashonaland Central Province of Zimbabwe. - Kasowe, Rittah (IJRDO- Journal of Educational Research, 2019)
There is compelling evidence that the use of ICT in the teaching and learning positively influences learners’ academic achievement. Its benefits occur across all socio-economic classes.  In spite of its significance, the implementation of ICT appears to be of great importance to ODL students who have to use it in their learning at the university and also in the teaching and learning. This study was therefore designed to analyse factors affecting use of computer technology by ODL students studying at an Open and Distance learning university at the same time teaching in secondary schools. The study used the mixed methodology approach and descriptive survey design. The population of the study comprised 78 ODL students who are secondary school teachers. Systematic random sampling and purposive sampling were used to select 40  respondents and 5 participants. Data were collected and generated through the questionnaire, the interview and observation techniques. Frequency tables, graphs and descriptive statistics were used to present quantitative data while qualitative data was presented as transcripts and in themes. The study established that there is unavailability of material and infrastructure resources. There is lack of expertise on part of the teachers/facilitators. There is minimal usage of computers to enhance professional work by teachers. Teachers’ attitudes towards teaching using computers have a bearing on implementation of the innovation. Schools are facing financial problems to outsource computer gadgets and to construct computer laboratories. The study therefore recommends that ODL students need to embark on in-service training sessions or even attend computer short courses. Out dated computers, need to be replaced with modern ones which have more capacity. Schools should be subsidised by the government to acquire and built infrastructure Schools and the community need to be staff developed on ways of income generation